LA-12 overcomes confluence-dependent resistance of HT-29 colon cancer cells to Pt (II) compounds - Svihálková-Sindlerová, Lenka; Foltinová, Vendula; Vaculová, Alena; Horváth, Viktor; Soucek, Karel; Sova, Petr; Hofmanová, Jirina; Kozubík, Alois (Anticancer research, 2010)
BACKGROUND: LA-12 is a new platinum (IV) drug with promising cytotoxic effects in a wide range of cancer cell lines. Its confluence-dependent effects were compared with cisplatin (CDDP) and oxaliplatin (L-OHP) in HT-29 cells. MATERIALS AND METHODS: Cytotoxicity was determined by MTT test, eosin exclusion assay, and cell number quantification. The cell cycle was analysed using propidium iodide DNA staining (flow cytometry), apoptosis by phosphatidylserine externalisation (annexin-V assay), mitochondrial membrane potential by flow cytometry, nuclear morphology by means of fluorescence microscopy, and PARP cleavage by Western blotting. RESULTS: While L-OHP and CDDP were practically inactive in the subconfluent cell population, LA-12 showed a similar toxicity in both subconfluent and growing populations. All compounds induced apoptosis, although with different potentials. CONCLUSION: LA-12 was able to overcome confluence-dependent resistance of HT-29 cells observed for other platinum compounds, which may have potential therapeutic use in slowly growing tumours.
Keywords: Amantadine; Drug Resistance, Neoplasm; apoptóza; amantadin; vztah mezi dávkou a účinkem léčiva; cisplatina; Cisplatin; Apoptosis; Oxaliplatin; buněčná adheze; nádory tračníku; lidé; Antineoplastic Agents; protinádorové látky; Cell Adhesion; chemorezistence; oxaliplatin; organoplatinové sloučeniny; Colonic Neoplasms; Dose-Response Relationship, Drug; Adenocarcinoma; adenokarcinom; Organoplatinum Compounds; HT29 Cells; buňky HT-29; Humans